2015
DOI: 10.5935/0100-4042.20150080
|View full text |Cite
|
Sign up to set email alerts
|

Acetanilide: Solvent-Free Green Synthesis

Abstract: We described herein a solvent-free synthesis of acetanilide developed in the context of green chemistry. The synthetic approach consisted of the reaction of aniline with acetic anhydride without additives, while using smaller amounts of reagents and water than previously described for this undergraduate experiment. The E Factor was 0.6 by experienced chemists and 0.9 by students. ]]>

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
4

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 1 publication
0
2
0
4
Order By: Relevance
“…26 More importantly, several solid and liquid substituted aromatic amines were reactive under this catalyst and solvent-free condition, and afforded the corresponding known acetanilides 27 in an instantaneous reaction (for practical reason, the reaction time of 10 s was established), and some trends emerged from the results, Scheme 1. Thus, anilines ortho, meta and para substituted were tolerated (see acetanilides 3a-h), but the presence of a strong electron-withdrawing group at ortho position precludes amide formation even under conventional (90 °C, 24 h) or microwave heating (90 °C, 10 min), and the starting amine was recovered, as indicated for 1q in the "Limitations" of Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 More importantly, several solid and liquid substituted aromatic amines were reactive under this catalyst and solvent-free condition, and afforded the corresponding known acetanilides 27 in an instantaneous reaction (for practical reason, the reaction time of 10 s was established), and some trends emerged from the results, Scheme 1. Thus, anilines ortho, meta and para substituted were tolerated (see acetanilides 3a-h), but the presence of a strong electron-withdrawing group at ortho position precludes amide formation even under conventional (90 °C, 24 h) or microwave heating (90 °C, 10 min), and the starting amine was recovered, as indicated for 1q in the "Limitations" of Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…25 Therefore, we recently developed a practical solvent-free green synthesis of such compound to experimental courses. 26 However, a search in the literature revealed that when other substituted acetanilides are needed as starting material in the context of a research project, the preparation used is very similar to that of parent acentanilide, which is almost the same of one century ago, which uses large amounts of solvents and additives such as acetic acid and sodium acetate, for instance. [5][6][7][8][9][10][11][12][13][14][15][19][20][21][22][23][24] It should be pointed out that, although there are a few syntheses of acetanilides in the absence of solvent, it is always necessary the use of grinding or microwave heating in these previously described syntheses or, more recurrent, the use of catalyst such as morpholinium bisulfate, zirconyl triflate, tris(pentaflurophenyl)borate, anatase phase TiO 2 nanoparticles, or even the unconventional rice husk ash, Figure 2.…”
Section: Introductionmentioning
confidence: 99%
“…3 Para ampliar mais ainda o potencial da acetanilida como molécula didática, investigamos sua cloração sob a perspectiva da QV.…”
Section: Cloração Da Acetanilidaunclassified
“…2 Para isto, é necessário o desenvolvimento de experimentos que contemplem, por exemplo, a realização de reação na ausência de solventes 3,4 ou empregando o mais verde deles, a água, 5,6 bem como o uso de biomassa como material de partida/reagente 7 ou aparelhos e técnicas modernas como o uso de micro-ondas, 8 e até mesmo técnicas clássicas modernizadas. Neste último aspecto, a mecanoquímica é a nova fronteira da metodologia sintética.…”
Section: Introductionunclassified
See 1 more Smart Citation